Influencing Factor on School-Age Children’s Holistic Health Care Who Using Online Media by Working-Age Parents in Northeast Thailand - Atchariya Wonginchan; Juraporn Tangpukdee; Suphasak Wonginchan; Sureeporn Kearttiwongkru; Sujitra Konggungong (Advances in Public Health)
Background. Thailand tends to have more access to online media. In 2020, the northeastern region had the highest usage rate. Especially school-age children have the highest usage rate. If misused for a long time, the consequences can adversely affect health in many aspects. Their parents should closely supervise and monitor them for this health problem. However, parents have limitations in caring because they have to work a lot. The aim was to study factors that influence working-age parents in holistic health care (HHC) of school-age children using online media in northeast Thailand. Materials and Methods. This research was a descriptive study, with a sample of parent amount 222. The questionnaire performed an item-objective congruence (IOC) = 0.60–1.00, the content validity index (CVI) = 0.90, and the Cronbach’s alpha coefficient was 0.93. The data collected then include the characteristics, use of online media, health problems, and health care. Finally, data were analyzed using descriptive statistics, frequency, percentage, standard deviation, and multiple regressions. Result. The results of the study are factors that influenced HHC with statistical significance (p≤.001) including the child’s gender, the child’s age, the child’s class, the type of internet, activities, the device, and the device owner. In addition, it was holistic health problems of school-age children such as physical, emotional, social, and intellectual. Importantly, these could explain the variation for HHC of 21.2% (adjusted R2 = 0.212), and the standard error in the model estimation was 25.06 (SEE = 25.06). Conclusion. Factors that influence school-age children’s health care are beneficial to preventing and solving health problems by using online media. Parents or health care professionals can use it as a guide to develop more effective health care strategies and policies. Ultimately, it will help to promote better health for children in an ever-changing digital world.